Thermal stability of plasticized durian skin fibre biocomposite - Abd. Rashid, Siti Munirah Salimah; Anuar, Hazleen; Hassan, Noor Azlina; Mohd Apandi, Siti Nur E'zzati; Ali, Fathilah; Manshhor, Mohd Romainor (UR Publishers, 2018)
Packaging is an essential component in food industries. Packaging protects food from spoilage between processing and usage by the consumer. In this study, biocomposites of poly(lactic acid) (PLA) reinforced with durian skin fibre (DSF) were prepared by extrusion and compression moulding. Epoxidized palm oil (EPO) was added into PLA/DSF biocomposite as a plasticizer. The results showed that the thermal stability of PLA/DSF biocomposite with EPO has not much difference compared to without EPO. The degradation time of PLA/DSF biocomposite also faster after it was disposed to the landfill as it took around 65 days to degrade. Fourier transform infrared (FTIR) confirmed the stability of EPO where the oxirane group of EPO existed in the PLA/DSF biocomposite. Therefore, PLA/DSF biocomposite with addition of EPO can be effectively used for food packaging application.